Monetary policy spill-over from advanced market economies to emerging market economies - Do, Linh (2019)
This paper assesses the monetary policy spill-overs from the Advanced Market Econ-omies (AMEs) to the Emerging Market Economies (EMEs) by using linear regression models to estimate the association between the monthly changes in excess money supply in ten representative EMEs and the four largest AMEs which are the US, EMU, UK and Japan. The models estimated the different impacts of each AMEs on the EMEs and considered the role of unconventional monetary policy on the spill-overs. Moreo-ver, the economic-condition differences among the EMEs were also studied to analyze their heterogenous responses to shocks from the AMEs. We found that, there were significant spill-overs from the AMEs to EMEs, with the largest impact caused by the US, and the amplified effects from both QE and tapering events. Finally, countries with relatively lower financial development, financial openness and degree of exchange rate flexibility experienced larger monetary policy spill-over influences from the AMEs.